Development of home-based lifestyle modification program among post menopausal osteoporotic women - Nurumal, Mohd. Said; Nik Mohd Hatta, Nik Noor Kaussar; Md Isa, Muhammad Lokman; Sharifudin, Mohd Ariff; Daud, Azlina; Draman, Samsul; Ibrahim, Muhammad (2019)
Fragility fracture is extremely prevalent in older adults, and is known to have a staggering cost of treatment. Nearly 1 in 3 women, especially Post-Menopausal Women (PMW) over the age of 50, will develop fragility fracture in their lifetime. The increased incidence of fracture among PMW suggests that osteoporotic fracture is a significant cause of morbidity and mortality. The management of osteoporosis in PMW involves pharmacological intervention as well as non-pharmacological methods, particularly in providing education and preventive behaviour programs. Education materials that suit and are tailor- made for our local PMW population are currently limited. Information inside the booklet can assist users in memorizing, and guide their health education activities. Realizing the importance of developing educational resources based on local needs, this study aims to develop and validate bone health educational booklet for PMW in preventing fragility fracture. This research was conducted in 2016, covering needs assessment study by distributing questionnaires on Knowledge, Attitude and Practice (KAP), and an assessment of fracture risk factors by using the Fall Free Prevention Questionnaire (FFPQ), the Activity Specific and Balance (ABC) scale, and the Fracture Risk Assessment (FRAX) tool; followed by conducting a physical examination using the Time up and Go (TUG) test, the Bone Mineral Density (BMD) analyses, and the Blood Serum Calcium level among local PMW. The process was continued by establishing the booklet content by including the findings from the needs assessment study, drafting of text, designing of illustrations and layout, validation process by content experts and end users, followed by the process of revising, editing and proofreading of the text. The booklet was validated using content and face validity. As a result, the booklet shows an excellent content validity with 0.77 of the global Content Validity Index (CVI). The level of agreement within the experts (91.1% -100%) and representatives of the end users (100%) was excellent. Overall, all of the participating end users were satisfied with the booklet and found the booklet very useful in guiding them. In addition, improvements proposed by the experts were included and modification of the final version was made accordingly. Thus, this booklet can be considered as an instrument to promote the prevention of osteoporosis and fragility fracture among PMW.